2018
DOI: 10.20944/preprints201812.0284.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metrological and Critical Characterization of the Intel D415 Stereo Depth Camera

Abstract: Low-cost RGB-D cameras are increasingly used in several research fields including human-machine interaction, safety, robotics, biomedical engineering and even Reverse Engineering applications. Among the plethora of commercial devices, the Intel RealSense cameras proved to be among the best suitable devices, providing a good compromise between cost, ease of use, compactness and precision. Released on the market in January 2018, the new Intel model RealSense D415 has a wide acquisition range (i.e. ~160-10000 mm)… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 30 publications
(41 reference statements)
0
21
0
1
Order By: Relevance
“…This light device (55 g) with low battery consumption (300 mAh) can be easily attached to a small size drone. In [35], the authors characterized it. They reported that it is sufficiently accurate to acquire information at very close range (from 15 cm to 50 cm), so it is adequate for our purposes.…”
Section: Figure2: Drone Lidarmentioning
confidence: 99%
“…This light device (55 g) with low battery consumption (300 mAh) can be easily attached to a small size drone. In [35], the authors characterized it. They reported that it is sufficiently accurate to acquire information at very close range (from 15 cm to 50 cm), so it is adequate for our purposes.…”
Section: Figure2: Drone Lidarmentioning
confidence: 99%
“…The device was chosen for this task after extensive characterization to ensure its accuracy [24]; as indicated in [24], the raw data are filtered after the acquisition to obtain a less noisy result.…”
Section: System Architecturementioning
confidence: 99%
“…Active stereo is a vision technique in which stereo and structured light, or laser, are combined to benefit of the advantages of both the technologies [19,55,52,53]. A 3D sensor built according to this technology is equipped with two outdistanced cameras and a projector between them, usually working in IR spectrum.…”
Section: Active Stereoscopymentioning
confidence: 99%